Chemical Control of Male Pre-pupae and Adult Females of Margarodes prieskaensis (Jakubski) (Coccoidea : Margarodidae) on Grapevines - de Klerk, C.A. (South African Journal of Enology and Viticulture, 2016)
Various contact, fumigant and systemic pesticides were evaluated over three years in a field trial for the control of male pre-pupae and adult females of Margarodes prieskaensis on grapevines. Cadusafos at 25 mL/m² gave excellent control of male pre-pupae. Pre-pupae, as well as adult females, were effectively controlled by dichloropropene at 15 mL/m², as well as by thiamethoxam at 2.4 mL/m² and 2.0 mL/m² and imidacloprid at 15 mL/m², 3.0 mL/m² and 1.5 mL/m². Contact and fumigant applications were made during March and April (beginning of leafdrop), and systemics during January (one month after harvest). Chlorpyrifos, furfural, fenamiphos, carbofuran and terbufos were found to be ineffective for the control of M. prieskaensis.